2006
DOI: 10.1093/brain/awl070
|View full text |Cite
|
Sign up to set email alerts
|

Impaired anticipatory control of fingertip forces in patients with a pure motor or sensorimotor lacunar syndrome

Abstract: We examined planning and execution of precision grasp in eight right-handed patients with a right pure motor or sensorimotor lacunar syndrome after a subcortical stroke and eight age-matched controls as they grasped and lifted an instrumented object whose weight could be varied without altering its visual appearance. Grip (normal) and load (tangential) forces at the fingertip-object interface were measured and the grip force rate (GFR) and load force rate (LFR) were derived. Planning of precision grasp was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
102
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 65 publications
4
102
1
2
Order By: Relevance
“…Similar to the healthy children and adults, children with CP were able to transfer the anticipatory control between the two hands; following several lifts with the noninvolved hand, anticipatory control, reflected by force rates that appropriately reflect the object's weight, is immediately present in the involved hand (10). A similar transfer from the non-involved to the involved hand has been observed in adults with hemiplegia (11). Based on this finding, it was hypothesized that the impaired anticipatory control in the involved hand is the result of impaired or indistinct sensory mechanisms signaling the object's physical characteristics (10,12).…”
mentioning
confidence: 62%
“…Similar to the healthy children and adults, children with CP were able to transfer the anticipatory control between the two hands; following several lifts with the noninvolved hand, anticipatory control, reflected by force rates that appropriately reflect the object's weight, is immediately present in the involved hand (10). A similar transfer from the non-involved to the involved hand has been observed in adults with hemiplegia (11). Based on this finding, it was hypothesized that the impaired anticipatory control in the involved hand is the result of impaired or indistinct sensory mechanisms signaling the object's physical characteristics (10,12).…”
mentioning
confidence: 62%
“…However, a clear difference in PLFR values between light and heavy objects was not seen in a population of patients with stroke despite several practice trials suggesting a lack of feedforward control poststroke (Raghavan et al 2006). However, the degree of impairment of feedforward control and the reason for the impairment have been difficult to quantify.…”
Section: Discussionmentioning
confidence: 96%
“…Force and EMG data were imported to and processed with MATLAB (The MathWorks, Natick, MA). Both grip and load forces were measured, but for the purpose of this study the computations pertain to load forces only, because it has been shown that when the friction at the grip surface is constant, feedforward control to object weight depends on the load forces (Raghavan et al 2006). Object liftoff was determined from the plate signals.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although neurorehabilitation is based on the assumption that patients can still learn, 5 relatively few studies have examined the effect of brain or spinal injury on motor learning itself. [6][7][8] It is a formidable challenge to compare learning capacity between groups with different initial levels of performance. If learning curves are compared, as was done in this study, the result can go in opposite directions depending on whether additive or multiplicative measures are used to assess learning.…”
mentioning
confidence: 99%